2017
DOI: 10.1002/gsj.1182
|View full text |Cite
|
Sign up to set email alerts
|

Network information and cross‐border M&A activities

Abstract: Research Summary How information about social networks affects firms’ global expansion is an important but rarely investigated question. We argue that different sources of network information will affect a firm's investment activities in the global market, but their relative importance may vary. Moreover, the influence of network information can be bounded by the global trade network. The results from a sample of cross‐border merger and acquisition (M&A) activities conducted by U.S. publicly listed firms revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 103 publications
(203 reference statements)
0
23
0
Order By: Relevance
“…Thus, starting in the hierarchies, we have the analysis by Minbaeva and Santangelo (2018) of how multinationals manage knowledge transfer across borders and the role that boundary spanners play. We then move to two analyses of cross-border mergers and acquisitions: the study by Xia, Ma, Tong, and Li (2018) on how the experience gained via the network of relationships of the firm supports its cross-border mergers and acquisition; and the study by Ellis, Lamont, Holmes, Ro, Faifman, DeGhetto, and Parola (2018) on the role that distances in informal and formal institutions between home and host play on mergers and acquisitions. We then jump to the study of cross-border alliances with the analysis by Pesch and Bouncken (2018) on international alliances and how cultural intelligence facilitates them.…”
Section: Methods To Conduct Economic Relationships Across Bordersmentioning
confidence: 99%
“…Thus, starting in the hierarchies, we have the analysis by Minbaeva and Santangelo (2018) of how multinationals manage knowledge transfer across borders and the role that boundary spanners play. We then move to two analyses of cross-border mergers and acquisitions: the study by Xia, Ma, Tong, and Li (2018) on how the experience gained via the network of relationships of the firm supports its cross-border mergers and acquisition; and the study by Ellis, Lamont, Holmes, Ro, Faifman, DeGhetto, and Parola (2018) on the role that distances in informal and formal institutions between home and host play on mergers and acquisitions. We then jump to the study of cross-border alliances with the analysis by Pesch and Bouncken (2018) on international alliances and how cultural intelligence facilitates them.…”
Section: Methods To Conduct Economic Relationships Across Bordersmentioning
confidence: 99%
“…The effect was even stronger when firm-specific uncertainty was higher. A strategic outcome of global alliance networks was studied by Xia, Ma, Tong, and Li (2018), who demonstrate that interlocking partners affect MNCs' cross-border acquisitions more than do joint venture partners, due to superior information conveyed by interlocked global networks. Sharma, Kumar, Yan, Borah, and Adhikary (2019) examine the performance outcomes of MNC buyer-supplier networks in 28 countries and show that density negatively affects the MNC's total international revenues, while centralization and average clustering coefficient influence the outcome via inverted-U-and U-shaped relationships, respectively.…”
Section: Interfirm Network Outcomesmentioning
confidence: 99%
“…Interlocking directors are widespread and common in companies, and, compared to obtaining information from social media or consultancies, they make it possible for a firm to access the interlocking partner's board and to acquire more reliable and complete information about their experiences of investing in foreign markets (Tuschke et al, 2014;Zona et al, 2018). Relatedly, Xia et al (2017) observed that the number of CBAs conducted by an acquirer in a country is positively related to the number of CBAs that its interlocking partner has had in that country. Therefore, this paper explores how an entrepreneur promotes their firm's international competitiveness-especially with respect to completing a CBA-through vicarious learning from their interlocking partners.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…An interlocking company represents a "conduit of information" (Useem, 1984) that could provide knowledge about how to manage country-specific acquisition issues and deal with foreign stakeholders, such as governments, communities, and local customers (Francis et al, 2014). Xia et al (2017) found that, if network partners have engaged in a CBA in a particular country, knowledge and experience in respect of that country will have been generated, and the firm which aims to undertake a future CBA may benefit from this network relationship and perform better by adopting the same strategy in that country.…”
Section: Hypotheses Development Knowledge Acquisition: Vicarious Learmentioning
confidence: 99%